TRANSFORMASI PERAN GENDER MELALUI PROGRAM PENINGKATAN PERANAN WANITA MENUJU KELUARGA SEHAT SEJAHTERA DI KECAMATAN TAPOS KOTA DEPOK: GENDER ROLE TRANSFORMATION THROUGH A WOMEN'S ROLE IMPROVEMENT PROGRAM TOWARDS HEALTHY AND PROSPEROUS FAMILIES IN TAPOS DISTRICT, DEPOK CITY - Salsabila, Najwa Inaya; Prihatini, Rini Laili (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2025)
Abstract: as awareness of gender equality increases, women are increasingly playing a role in the public sphere. However, the Global Gender Gap Report 2024 highlights the remaining gaps, exacerbated by traditional norms and patriarchal culture. Despite the efforts made, there are still gaps in the understanding and implementation of balanced and equitable gender roles. This research aims to explore how the gender roles of female inmates are changing in the integrated P2WKSS program in Tapos District, Depok City. This research adopts a theory sourced from Caroline ON's typology of gender roles. Moser and relevant perspectives of feminism. The research methodology used is qualitatively descriptive, with data collection through in-depth interviews, direct observation, and a Focus Group Discussion (FGD) with informants consisting of women from vulnerable groups, cadres, and groups of women farmers in Cilangkap Village, as well as related parties. Data analysis was carried out through triangulation to ensure informant validity. Research shows that the gender roles of female inmates experience positive changes in productive, reproductive and social aspects of society. Despite the increase in skills and knowledge, the impact on their work has been insignificant, and they still face a double burden in their domestic role. Constraints encountered during the programme point to the challenge of timing between these roles. However, the continued activeness of the post-program women's farmer group shows that the P2WKSS program has succeeded in increasing the role of women, even though gender role justice has not been fully realized due to deep-rooted culture and traditions. Abstrak: seiring meningkatnya kesadaran akan kesetaraan gender, perempuan semakin berperan di ranah publik. Namun, Global Gender Gap Report 2024 menyoroti kesenjangan yang masih ada, diperparah oleh norma tradisional dan budaya patriarki. Meskipun berbagai upaya telah dilakukan, masih terdapat gap dalam pemahaman dan implementasi peran gender yang seimbang dan adil. Penelitian ini bertujuan untuk mengeksplorasi bagaimana perubahan peran gender perempuan warga binaan dalam program terpadu P2WKSS di Kecamatan Tapos Kota Depok. Penelitian ini mengadopsi teori yang bersumber dari tipologi peran gender Caroline O.N. Moser dan perspektif feminisme yang relevan. Metodologi penelitian yang digunakan adalah kualitatif deskriptif, dengan pengumpulan data melalui wawancara mendalam, observasi langsung, dan Focus Group Discussion (FGD) dengan informan yang terdiri dari perempuan kelompok rentan, kader, dan kelompok wanita tani di Kelurahan Cilangkap, serta pihak terkait.Analisis data dilakukan melalui triangulasi untuk memastikan validitas informan. Penelitian menunjukkan bahwa peran gender perempuan warga binaan mengalami perubahan positif dalam aspek produktif, reproduktif, dan sosial kemasyarakatan. Meskipun terdapat peningkatan keterampilan dan pengetahuan, dampak terhadap pekerjaan mereka tidak signifikan, dan mereka masih menghadapi beban ganda dalam peran domestik. Kendala yang dihadapi selama program menunjukkan tantangan dalam mengatur waktu antara peran-peran tersebut. Namun, keberlanjutan keaktifan kelompok wanita tani pasca-program menunjukkan bahwa program P2WKSS berhasil meningkatkan peran wanita, meskipun keadilan peran gender belum sepenuhnya terealisasi akibat budaya dan tradisi yang mengakar.